Effect of a specific nursing intervention programme on relapse prevention of clients with alcohol dependence syndrome - Jose, Suma; Selvam Venkatakrishnan, Indra (International Journal of Nursing Research, 2023)
Aim: The present study was aimed at assessing the effectiveness of structured intervention programme on relapse of clients with alcohol dependence syndrome admitted in a selected hospital, Ernakulam, Kerala. The investigator had a chance to interact with alcohol dependent clients during the clinical experience in De-addiction ward. An interest to bring these clients and family back to normal life made the investigator find out the effect of a specific nursing intervention programme on relapse prevention of clients with alcohol dependence syndrome. Materials and Methods: The sample consisted of 60 clients with alcohol dependence syndrome, who were admitted in the de-addiction ward, and the subjects were selected by systematic random sampling method. Results: The study aimed to determine the effects of a specific nursing intervention programme on relapse of clients with alcohol dependence syndrome. At the end of the study, based on the effectiveness specific nursing intervention programme could be implemented in the management of clients with alcohol dependence syndrome which will improve motivation and prevent relapse. Conclusion: Being an active and qualified member of the psychiatric multidisciplinary team, the nurses can be the best providers their interventions. Based on the findings of the study, it is concluded that specific nursing intervention programme can significantly improve the prevention of relapse of clients with alcohol dependence syndrome.